Geochemical Provenance, Source Area Weathering, and Tectonic Setting of the Bida Sandstone in the Northern Bida Basin, Northcentral Nigeria - Vincent Odigo; God’swill Nathan Sambo (Indonesian Journal on Geoscience, 2023)
This paper aims to determine the geochemical provenance, source area weathering, and tectonic setting of the Bida sandstone exposed at Doko and Jima in the Northern Bida Basin, Northcentral Nigeria. Geological fieldwork was carried out and sandstone samples were collected and analyzed for major element concentrations using X-Ray Fluorescence (XRF) method. Major element abundance shows that the studied sandstone samples consist of SiO2 (average 71.42%), Al2O3 (average 15.16%), and CaO (average 0.26%) constituting about 90% of the bulk rock composition. While P2O5, Na2O, K2O, MgO, TiO2, MnO, and Fe2O3 constitute about 10% of the composition. The results obtained using the Al2O3/TiO2 ratios show that the sandstones derived from intermediate to felsic igneous rocks. The A-CN-K triangular diagram shows that majority of the analyzed samples plotted on the aluminum zone towards kaolinite shows predominantly intermediate degree of weathering except for one sample which falls towards the CN-K line, indicating the different degree of weathering (perhaps an existence of differential weathering in the area). The source area weathering indices which include CIA (68.6%), CIW (71.20%), and PIA (54.66%) further confirms that the sediments have been subjected to intermediate weathering. The K2O/Na2O versus SiO2 tectonic setting discriminant plot shows that the samples are dominantly deposited in the passive margin setting. It is, therefore, concluded that the Bida sandstone analyzed was sourced from predominantly felsic igneous rocks where the degree of chemical weathering was intermediate and in the passive margin setting.